Pengaruh Pertumbuhan Laba dan Dana Syirkah Temporer terhadap Maqashid Syariah pada Bank Umum Syariah Periode 2021-2023 - Nurhayati, Sri; Sidi, Yudi Priambodo Purnama; Harris, Allan (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
The purpose of the study was to see the effect of profit growth and temporary syirkah funds with Maqasyid Syariah in 2021-2023. Maqasyid Syariah can be interpreted as ownership of a company that can be seen from the value of its shares. While Bank Umum Sariah can be interpreted as a bank that operates based on Sharia principles and all its operations are based on the Quran and Hadith and there is a halal guarantee in its transactions. The methods used are quantitative verification and descriptive. With a total sample of 24. The results of this study are the Probability Value of X1 (Profit Growth) > 0.5 with a Coefficient value of -0.0001, meaning that the variable X1 (Profit Growth) has no effect on Maqasyid Syariah. The Probability Value of X2 (Temporary Syirkah Funds) <0.5 with a Coefficient value of 1.02E-08 means that the variable X2 (Temporary Syirkah Funds) has an effect on Maqasyid Syariah. The F-statistic value <0.05, meaning that simultaneously or together, variables X1 and X2 have an effect on Maqasyid Syariah. The R-squared value is 0.879 or 87.9%, meaning that variables X1 and X2 are able to provide an influence of 87.9% on Maqasyid Syariah. The rest is influenced by other factors